2009
DOI: 10.1007/s10863-009-9229-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionine dietary supplementation on mitochondrial oxygen radical generation and oxidative DNA damage in rat liver and heart

Abstract: Methionine restriction without energy restriction increases, like caloric restriction, maximum longevity in rodents. Previous studies have shown that methionine restriction strongly decreases mitochondrial reactive oxygen species (ROS) production and oxidative damage to mitochondrial DNA, lowers membrane unsaturation, and decreases five different markers of protein oxidation in rat heart and liver mitochondria. It is unknown whether methionine supplementation in the diet can induce opposite changes, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 65 publications
1
42
0
3
Order By: Relevance
“…On the other hand, excessive intake of dietary methionine is toxic. This toxicity far exceeds that produced by any other amino acid, 61 leading to damage in some vital organs and increases in tissue oxidative stress 62,63 with similar negative effects to those observed in rats fed diets with a high protein content. Chronic and excessive methionine supplementation increases plasma hydroperoxides and low-density lipoprotein cholesterol, 64 induces vascular 65 and kidney damage with tubular hypertrophy, 66 raises iron accumulation and lipid peroxidation, and leads to liver dysfunction, 67 besides other alterations in other organs.…”
Section: Effect On Longevitymentioning
confidence: 92%
“…On the other hand, excessive intake of dietary methionine is toxic. This toxicity far exceeds that produced by any other amino acid, 61 leading to damage in some vital organs and increases in tissue oxidative stress 62,63 with similar negative effects to those observed in rats fed diets with a high protein content. Chronic and excessive methionine supplementation increases plasma hydroperoxides and low-density lipoprotein cholesterol, 64 induces vascular 65 and kidney damage with tubular hypertrophy, 66 raises iron accumulation and lipid peroxidation, and leads to liver dysfunction, 67 besides other alterations in other organs.…”
Section: Effect On Longevitymentioning
confidence: 92%
“…The mean contents of isoleucine were 30.53 mg/g in J. sigillata and 30.24 mg/g in J. regia. A research showed that methionine supplement in the diet specifically increased mitochondrial ROS production and mitochondrial DNA oxidative damage in rat liver mitochondria offering a plausible mechanism for its hepatotoxicity (Gomez et al, 2009) In all the determined essential amino acids, the mean content of leucine was the highest, corresponding the research by Wu et al (2007).…”
Section: Compositions Of Essential Amino Acidsmentioning
confidence: 67%
“…It is important to note that Western human populations generally consume levels of Met that are several-fold higher in comparison to dietary requirements (Sanz et al 2006;Gomez et al 2009). The negative effects of Met on lifespan have been strongly related with the unpleasant ability of this amino acid to promote oxidative stress, which is implicated in the mechanism of aging.…”
Section: Resultsmentioning
confidence: 99%
“…The negative effects of Met on lifespan have been strongly related with the unpleasant ability of this amino acid to promote oxidative stress, which is implicated in the mechanism of aging. Met restriction strongly decreases the production of reactive oxygen species in mitochondria, as well as oxidative damage in proteins, membranes and mitochondrial DNA, while increased supplementation of Met shows just the opposite effects (Orentreich et al 1993;Sanz et al 2006;Gomez et al 2009). However, the mechanisms via which Met acts in such a manner in mammalian cells are not understood.…”
Section: Resultsmentioning
confidence: 99%